Analysis of Student Satisfaction with Digital-Based Learning Media Assisted by Baamboozle - Nurhasanah, Sifa; Muhammad, Taofik; Taufiq, Muhammad (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2025)
This study evaluates student satisfaction with Baamboozle educational game-based learning media among fifth-grade students. The research employed quantitative descriptive methods using a 5-point Likert scale questionnaire administered to 18 students at SDN 1 Cihaurbeuti. Data analysis through Jamovi software revealed varying satisfaction levels across three measured aspects. Students rated user experience and application performance as